The Effect of Antibiotic Prophylaxis on Post-Operative Infection in Patients Undergone Flexible Cystos-copy - Arrabal-Polo, Miguel Angel; Cano-García, María del Carmen; Arrabal-Martín, Miguel; Merino-Salas, Sergio (Urology Journal, 2017)
Purpose: The aim of this study is to determine whether antibiotic prophylaxis is required in this outpatient procedure. Materials and Methods: A non-randomised, prospective observational study that included 184 patients subjected to flexible cystoscopy divided into three groups: - Group 1:60 patients with prophylaxis of 500 mg of ciprofloxacin;- Group 2:62 patients with prophylaxis of 3 g of phosphomycin; and Group 3:62 without antibiotic prophylaxis. Prior to inclusion in the study, absence of infection was checked by means of a urine culture obtained 7 days before the procedure. An analysis was made of urinary infection after 7 days, the cystoscopy indications and its diagnosis, the presence of comorbidities, and the urinary symptoms during the following 7 days. Results: The mean age of the patients in Group 1 was 65.3 (SD: 12.5) years, 66.7 (10.8) years in Group 2, and 66.9 (10.8) years in Group 3 (P = .7). Bacteriuria was present in 15% of the patients in Group 1, compared to 22.6% in Group 2, and 12.9% in Group 3, with the differences not statistically significant. In multivariate analysis, it was observed that there was no association with the appearance of bacteriuria between the groups for age (P = .8), diabetes (P = .2), smoking (P = .4), lower urinary tract symptoms (P = .7), or immunosuppression (P = .6). Conclusion: The use of ciprofloxacin or phosphomycin as prophylaxis does not appear to be indicated in flexible cystoscopy in our health area.